2015
DOI: 10.1371/journal.pcbi.1004151
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of White-Plague Coral Disease in Climate Change Scenarios

Abstract: Coral reefs are in global decline, with coral diseases increasing both in prevalence and in space, a situation that is expected only to worsen as future thermal stressors increase. Through intense surveillance, we have collected a unique and highly resolved dataset from the coral reef of Eilat (Israel, Red Sea), that documents the spatiotemporal dynamics of a White Plague Disease (WPD) outbreak over the course of a full season. Based on modern statistical methodologies, we develop a novel spatial epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The established pattern of high prevalence of white-plague disease following thermal anomalies suggests that thermal-stress events are the seasonal drivers of white-plague disease outbreaks, and that coral bleaching most likely enhances the severity of the disease. The above interpretation also suggests that the impact of coral diseases will increase with future global warming 4 38 .…”
Section: Discussionmentioning
confidence: 90%
“…The established pattern of high prevalence of white-plague disease following thermal anomalies suggests that thermal-stress events are the seasonal drivers of white-plague disease outbreaks, and that coral bleaching most likely enhances the severity of the disease. The above interpretation also suggests that the impact of coral diseases will increase with future global warming 4 38 .…”
Section: Discussionmentioning
confidence: 90%
“…It is plausible, therefore, that discontinuities in mosaic marine habitats such as coral reefs, seagrass meadows and oyster reefs similarly affect disease spread in the ocean. In coral reefs, several studies have shown associations between colony configuration and clustering of disease cases [10][11][12][13], while other studies have found no evidence of disease clustering [4]; these opposing results probably reflect differences in modes of transmission for different diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Information on the dispersal patterns of coral diseases is limited, although some researchers have analyzed the transmission pattern of diseased colonies using spatial analyses (Jolles et al 2002;Foley et al 2005;Zvuloni et al 2009;Lentz et al 2011;Zvuloni et al 2015). Coral diseases such as sea fan aspergillosis and yellow band disease have exhibited clustering at a small spatial scale .…”
Section: Analysis Of Bbd Bandsmentioning
confidence: 99%
“…These data are utilized to elucidate not only ecological factors contributing to the reduction of coral reefs on both global and regional scales (Osborne et al 2011;Ruiz-Moreno et al 2012), but also , Nobuhiro MANO 1 *, Yukio YANAGISAWA 1 , and Tsukasa MORI characteristics of the spread of infection in the population on regional and local scales (Miller et al 2003;Sato et al 2009;Pollock et al 2014;Lamb et al 2014). Some researchers have also focused on the pattern of spatial distribution of diseased colonies for analysis of infectious transmission on a local scale (Jolles et al 2002;Foley et al 2005;Zvuloni et al 2009;Lentz et al 2011;Zvuloni et al 2015).…”
Section: Introductionmentioning
confidence: 99%